2015
DOI: 10.5672/apunts.2014-0983.es.(2015/3).121.04
|View full text |Cite
|
Sign up to set email alerts
|

La pertinencia educativa de las habilidades gimnásticas: apreciaciones del profesorado

Abstract: Resumen Esta investigación analiza los valores educativos que identifica el profesorado de educación física en la docencia de las habilidades gimnásticas y acrobáticas. Adicionalmente, indaga qué modalidades gimnásticas son las más pertinentes para él por los valores y beneficios que aportan. El estudio se encuadra en el enfoque cualitativo y se utiliza el software AQUAD 6 para el análisis de los datos. Los resultados evidencian que los participantes perciben que las destrezas gimnásticas promueven en el alumn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…AG is considered to be an excellent cooperative and integrative proposal for motor and attitudinal development [37,63]. Moreover, Physical Education teachers identify this modality as the most suitable for developing personal and social values in students and say that it can favour their teaching-learning process due to its high collaborative component, thus minimising the personal differences between classmates [32]. In the study carried out by Piepiora, Piepiora and Bagi ńska [16] on the relationship between sport practice and personality development, they concluded that the more sport, the greater the openness to experience, kindness and awareness, considering the importance of establishing educational proposals based on the formation of personality from PE classes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…AG is considered to be an excellent cooperative and integrative proposal for motor and attitudinal development [37,63]. Moreover, Physical Education teachers identify this modality as the most suitable for developing personal and social values in students and say that it can favour their teaching-learning process due to its high collaborative component, thus minimising the personal differences between classmates [32]. In the study carried out by Piepiora, Piepiora and Bagi ńska [16] on the relationship between sport practice and personality development, they concluded that the more sport, the greater the openness to experience, kindness and awareness, considering the importance of establishing educational proposals based on the formation of personality from PE classes.…”
Section: Discussionmentioning
confidence: 99%
“…Gymnastic skills promote personal and social values and abilities in students, such as self-esteem, responsibility, confidence, cooperation, teamwork and self-management of fears and insecurities [32,64]. Previous research has found that AG is an appropriate modality for promoting values among adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations